Corporate social responsibility and internal stakeholders' health and well-being in Europe: a systematic descriptive review
Corporate social responsibility (CSR) can contribute to the triple bottom line of economic, social and environmental performance in organizations. However, the relationship between CSR, employee health and well-being has not been frequently assessed despite an increased awareness that this relationship can contribute to sustainable workplaces. To identify studies addressing the relationship between CSR and employee health and well-being within the EuCIropean context, we conducted a systematic literature search using Web of Science and Medline. Of the 60 articles screened for inclusion, 16 were retained. The results suggest that the majority (n = 14) of the identified studies aimed to understand the impact of CSR strategies on employees’ job satisfaction. None of the studies investigated the relationship between internal CSR and physical health. There was no clarity in the measurement of either internal CSR or the extent to which it affected employee outcomes. There is a need for consensus on measurement of internal CSR and of the health and well-being-related outcomes. Public health and occupational health researchers should be part of the discussion on the potential role of CSR in physical and psychological health outcomes beyond job satisfaction.